Cointegration analysis of indirect taxes and economic growth in the Republic of Serbia - Branimir Kalaš; Vera Mirović; Jelena Andrašić (Anali Ekonomskog fakulteta u Subotici, 2020)
This research examines the relationship between indirect taxes and gross domestic product per capita in the Republic of Serbia from 2005 to 2019. The aim of this paper is to evaluate the long-run relationship between value added tax, excises and gross domestic product per capita based on Johansen cointegration test. The empirical analysis includes descriptive statistics, unit root test, cointegration test and FMOLS model. The results reveal a long-run relationship between indirect taxes such as value added tax and excises and the gross domestic product per capita in the Republic of Serbia for the observed period. Empirical findings confirm that revenues of value added tax and excises have positive and significant effect on the gross domestic product per capita in the long-run.